A.H. Gerhard : vrijdenker, socialist en opvoeder : een keur van zijn opstellen. - Gerhard, A.H.; Spigt, P.; Reinalda, M.A. (Amsterdam : Arbeiderspers, 1949)
Collectie Vrijzinnige Werkmansbibliotheek
Nederlands
Monografie
Keywords: Vrijzinnige Werkmansbibliotheek